Protein characterisation and antioxidant potential of fresh cheese obtained by kombucha inoculum - Bjekić, Maja (Array, 2021)
Protein profile, in vitro gastrointestinal digestion and antioxidant potential of two fresh cheese samples obtained by kombucha inoculum and traditional starter culture have been investigated in this study. There is a significant difference in protein profile and bioactive potential between fresh cheese samples. Kombucha fresh cheese contains higher proportion of protein, predominantly the casein fractions (α-casein and β-casein) compared to fresh cheese obtained by traditional culture. After gastrointestinal digestion (with pepsin and pancreatin), significantly higher amount of soluble protein and higher degree of hydrolyses were measured in kombucha fresh cheese sample than sample obtained by traditional culture. During gastrointestinal digestion, for fresh cheese with traditional starter both fractions of casein are degraded more rapidly by pepsin than in kombucha fresh cheese. The hydrolysates of cheese obtained by kombucha inoculum showed higher phenolic content and higher antiradical scavenging abilities than hydrolysates of fresh cheese produced with traditional starter. These results suggest that kombucha inoculum contributes to improvement of product"s bioactive potential.